Silver nanoparticles: Their role as antibacterial agent against Aeromonas salmonicida subsp. salmonicida in rainbow trout (Oncorhynchus mykiss). (August 2018) - Shaalan, Mohamed; El-Mahdy, Magdy; Theiner, Sarah; Dinhopl, Nora; El-Matbouli, Mansour; Saleh, Mona
Abstract: The rise of bacterial resistance to antibiotics is one of the great challenges of our age. One of the strategies to limit the development of antibiotics resistance is the investigation of alternative antimicrobials. As silver nanoparticles demonstrated a potent bactericidal activity in vitro, the aim of this study was to evaluate the in vivo antibacterial activity of silver nanoparticles against Aeromonas salmonicida subsp. salmonicida . Rainbow trout (n = 120) were divided into four groups of 30 fish each. First group was challenged with A . salmonicida (Positive control), the second group was challenged with A . salmonicida and exposed to silver nanoparticles by immersion for three hours (100 μg/L), the third group was challenged with A . salmonicida and intraperitoneally injected with silver nanoparticles (17 μg/mL) and the fourth group was sham-treated and served as a negative control group. At the 7th day post challenge, histopathology of the positive control group revealed the presence of bacterial aggregates in tissues with degenerative and necrotic changes, while at the 35th day post challenge, only liver necrosis persisted. Silver nanoparticles-treated and negative control groups did not show any clinical signs, mortalities or histopathological alterations and they were tested negative for A . salmonicida . The immersion in silver nanoparticles did not result in detectable residues of silver in the muscles 35 days after treatment. These findings demonstrate the antibacterial properties of silver nanoparticles against A . salmonicida infection. Therefore, they could be used for development of antibacterial agents in aquaculture. Highlights: Silver nanoparticles show in vivo antibacterial action against Aeromonas salmonicida . Nanosilver immersion and I/P injection prevented A . salmonicida infection No adverse histopathological lesions were observed after nanosilver treatment. Silver was not detected in fish muscles 35 days post silver nanoparticles immersion.